1997
DOI: 10.1002/pro.5560060413
|View full text |Cite
|
Sign up to set email alerts
|

Limited proteolysis of ribonuclease A with thermolysin in trifluoroethanol

Abstract: We have examined the proteolysis of bovine pancreatic ribonuclease A (RNase) by thermolysin when dissolved in aqueous buffer, pH 7.0, in the presence of 50% (v/v) trifluoroethanol (TFE). Under these solvent conditions, RNase acquires a conformational state characterized by an enhanced content of secondary structure (helix) and reduced tertiary structure, as given by CD measurements. It was found that the TFE-resistant thermolysin, despite its broad substrate specificity, selectively cleaves the 124-residue cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 86 publications
1
12
0
1
Order By: Relevance
“…Presumably, in the absence of TFE, the 29 kDa fragment undergoes further proteolysis to yield the 17 and 13 kDa fragments. The resistance of thermolysin, a thermophilic protease, in the presence of TFE and organic solvents has been previously noted [23,34,35] and our results showed that thermolysin retains 90% of its initial activity in 40% of TFE concentration.…”
Section: Proteolytic Digestion Of Bla and Baasupporting
confidence: 51%
See 4 more Smart Citations
“…Presumably, in the absence of TFE, the 29 kDa fragment undergoes further proteolysis to yield the 17 and 13 kDa fragments. The resistance of thermolysin, a thermophilic protease, in the presence of TFE and organic solvents has been previously noted [23,34,35] and our results showed that thermolysin retains 90% of its initial activity in 40% of TFE concentration.…”
Section: Proteolytic Digestion Of Bla and Baasupporting
confidence: 51%
“…The results of this study and previous investigations [23,34] show that the proteolysis of proteins by thermolysin in the presence of TFE can be used to achieve selective fragmentation of proteins. As shown by Fontana et al [23,34], limited digestion of proteins such as cytochrome c, lysozyme and ribonuclease A with thermolysin in the presence of TFE can be considered as a valuable procedure to produce large fragments which can be used for sequencing [35] and evaluation of structure-activity relationship in proteins [32,33].…”
Section: Proteolytic Digestion Of Bla and Baamentioning
confidence: 79%
See 3 more Smart Citations